Formação continuada de professores de educação física em prevenção à obesidade infantil: uma proposta formativa de base frankliana - Araújo, Jairo Silva de (2023)
The training of Physical Education teachers presents challenges, especially when it comes to the prevention of childhood obesity, because when one thinks about obesity, the biological aspect of this problem is primarily brought to mind. In an approach that goes beyond this aspect, this research brings to the discussion Viktor Frankl's theory, which considers the human being formed by three dimensions: biological/somatic; psychological/animistic, and noetic/spiritual. Such dimensions were the basis for proposing a training course, based on the following research problem: experiences that can be experienced by Physical Education teachers in a training course on childhood obesity prevention, in the light of the franklian theory? It was established as a general objective: to investigate the experiences of Physical Education teachers in a course of prevention of childhood obesity, in the light of the Franklian theory and, as specific objectives: 1) to articulate the concepts of continued formation of Physical Education teachers, theory of Viktor Frankl and childhood obesity; 2) design, for implementation and evaluation, a continuing education course for Physical Education teachers in preventing childhood obesity, in the light of Viktor Frankl's theory; 3) explain the experiences experienced by Physical Education teachers participating in the training course, and 4) systematize the training course implemented, an educational product of the research, in accordance with CAPES requirements for professional master's degrees in teaching. The participants of the research, carried out in the distance modality, were 14 Physical Education teachers from the State Secretariat of Education and Sports of Amazonas (SEDUC-AM). A qualitative research was carried out in which the method used for data production was action research (TRIPP, 2005), in four phases: 1) diagnosis; 2) planning; 3) implementation, and 4) evaluation, using participant observation and conversation as techniques and instruments, respectively; field journal; monitoring of classes via Google Meet, and production of participants (preparation of lesson plans). To analyze the constructed data, Creswell (2014) was used to organize the analysis in three moments, namely: data organization; data coding, and data interpretation. The research results make it possible to explain the following experiences experienced by Physical Education teachers in the training course for preventing childhood obesity, in the light of the Franklian theory: 1) recognition of the importance of human three-dimensionality to overcome challenges facing the prevention of childhood obesity; 2) understanding of the importance of human three-dimensionality being related to the proposals of the BNCC for the prevention of childhood obesity and for the creation of new paths; 3) Perception of human three-dimensionality as a factor inherent to the human being, possible to be used in other circumstances.